(untitled) (Journal of the Bangladesh Agricultural University, 2016)
This study was undertaken to investigate the effect of sulphaclozine sodium and toltrazuril for the treatment of experimentally induced caecal coccidosis. Day-old chicks (n=96) reared in a coccidia free condition divided into six Groups (A, B, C, D, E and F) each having 4 subgroups of 4 chicks in each. At the age of 23 days the chicks were infected with 104 sporulated oocysts of E. tenella except control Group F and treated for 4 consecutive days from 3 days post infection. Then treatment was given in Group A (2 gm/L), B (3 gm/L) with sulphaclozine sodium and in Group C (1 ml/L), D (1.5 ml/L) with toltrazuril. Group E was maintained as infected, but untreated and Group F as negative control. After treatment Group A gained almost similar weight with Group F. A significantly higher (P<0.05) weight gain was recorded in Group A and B compared with Group C and D.The infected untreated chicks passed a large number of oocysts from day 5 till the end of the experiment. Chicks receiving sulphaclozine sodium (Groups A and B) had large oocysts count compared with the Groups C and D treated with toltrazuril but lower than the untreated chicks. At the end of experiment the lowest oocysts count was found in Group D (31.32 x 106) and highest in Group E (53.59 x106). Hence this study recommends to use sulphaclozine sodium and toltrazuril for chicken coccidiosis. J. Bangladesh Agril. Univ. 14(1): 57-61, June 2016